Analisis Faktor Keteraturan Ibu dalam Menimbang Balita di Posyandu - Florani Asanab; Ribka Limbu; Enjelita M. Ndoen (Journal of Health and Behavioral Science, 2019)
Mothers’ regularity of weighing their children aged <5 yo at Posyandu is crucial to monitor the growth, nutritional status, and health of the children. Several factors could affect mothers’ regularity in weighing their children at Posyandu. This study aimed to identify factors affecting mothers to regularly measure the weight of their children <5 yo at Posyandu in Toobaun Village Kupang District. The study used an analytical survey with a cross-sectional study design. The sample was 57 mothers who had under-five children obtained by simple random sampling technique. Data were collected through interviews using questionnaires and analyzed using the chi-square test. The result showed that knowledge (p= 0,002) and distance home-posyandu (p=0,000) associated with mothers’ regularity of weighing their under-five children, while mother’s occupation had no association with mothers’ regularity of weighing their children( p=0,091). Health workers should encourage mothers to measure regularly the weight of their under-five children at Posyandu.